Green Synthesis of Zinc Nanoparticles Using Phenolic Acids from Edible Mushrooms of Chhattisgarh Region: A Novel Approach - Tripathy, Parinita; Shahi, Sanyogita (Journal of Neonatal Surgery, 2025)
This study presents a novel and environmentally sustainable approach for synthesizing zinc nanoparticles (ZnNPs) by leveraging phenolic acids extracted from edible mushrooms endemic to the Chhattisgarh region. We prepared methanolic extracts from selected mushroom species and quantified their total phenolic content using the Folin–Ciocalteu method, complemented by high-performance liquid chromatography (HPLC) for comprehensive phenolic acid profiling. The biosynthesis of ZnNPs was achieved through a controlled reaction between these mushroom extracts and zinc acetate dihydrate. The synthesized nanoparticles underwent rigorous characterization using a suite of analytical techniques, including UV-Visible spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), and X-ray Diffraction1 (XRD) analysis. Our findings underscore the significant potential of native edible mushrooms as efficient and eco-friendly bio-factories for the production of ZnNPs, paving the way for their diverse applications in biomedical, agricultural, and environmental remediation sectors.